2022
DOI: 10.3389/fonc.2022.845931
|View full text |Cite
|
Sign up to set email alerts
|

The hnRNPK/A1/R/U Complex Regulates Gene Transcription and Translation and is a Favorable Prognostic Biomarker for Human Colorectal Adenocarcinoma

Abstract: Heterogeneous nuclear ribonucleoproteins (hnRNPs) are emerging as a crucially important protein family in tumors. However, it is unclear which family members are essential for cancer progression, and their diverse expression patterns and prognostic values are rarely reported. In this work, we found that the expression levels of hnRNPs were all upregulated in colon adenocarcinoma (COAD) and rectal adenocarcinoma (READ) tissues. Immunohistochemical staining revealed that hnRNPA1, hnRNPA2B1, hnRNPC, hnRNPK, hnRNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…It has been proposed that these proteins belong to distinct subgroups within the hnRNP family, where hnRNP A1 is involved in core complex formation and hnRNP K plays roles in RNA regulation [42] . Recently, it was shown that hnRNP A1, R, U, and K form a complex in colon and rectal adenocarcinoma cells, in which hnRNP K regulated translation of relevant genes [43] . When cross-referencing the published co-expression network of the hnRNP A1/R/U/K complex with the array hnRNP K data, we see that several genes identified are hits.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that these proteins belong to distinct subgroups within the hnRNP family, where hnRNP A1 is involved in core complex formation and hnRNP K plays roles in RNA regulation [42] . Recently, it was shown that hnRNP A1, R, U, and K form a complex in colon and rectal adenocarcinoma cells, in which hnRNP K regulated translation of relevant genes [43] . When cross-referencing the published co-expression network of the hnRNP A1/R/U/K complex with the array hnRNP K data, we see that several genes identified are hits.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers found that high expression of HNRNPR predicted increased OS rates in COAD based on the HPA webtool, although they did not explore the potential mechanism of HNRNPR in COAD or the effect of HNRNPR on cancer cells (Y. Li et al, 2022). Moreover, there is one report highlighting the role of the hnRNP family in pan-cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that HNRNPR overexpression correlated with 18F‐FDG uptake in ESCA, and HNRNPR expression could predict poor survival in ESCA patients (X. Y. Liu et al, 2022). The researchers found that high expression of HNRNPR predicted increased OS rates in COAD based on the HPA webtool, although they did not explore the potential mechanism of HNRNPR in COAD or the effect of HNRNPR on cancer cells (Y. Li et al, 2022). Moreover, there is one report highlighting the role of the hnRNP family in pan‐cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, other infection-specific LSD1 interactions may favor parasite survival, such as the splicing factor proline- and glutamine-rich (SFPQ), the ATP-dependent RNA helicase A (DHX9), and Matrin 3 (MATR3), and the non-POU domain-containing octamer-binding protein (NONO). These molecules are respectively involved in i) viral RNA amplification (Labeau et al, 2022), ii) nuclear retention of RNAs that are defective or immature (Zhang and Carmichael, 2001), iii) DNA non-homologous end joining (NHEJ) recombination required for double-strand break repair and V(D)J recombination (Salton et al, 2010) and iv) modulation of transcription and translation processes (Li et al, 2022). LSD1 interaction partners within infected macrophages were also enriched in ribosomal proteins, whose methylation state may be affected by LSD1 (Hamidi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%